Modified mRNA Encoding the Crimean-Congo Hemorrhagic Fever Virus Nucleocapsid Protein Confers Robust Protection Against Lethal Challenge in Mice - Keskin, Sercan; Pavel, Shaikh Terkis Islam; Sak, Rabia; Bahadori, Fatemeh; Aslan, Ahmet Furkan; Aktas, Munir; Doymaz, Mehmet Ziya (Wiley, 2026)
The Crimean-Congo Hemorrhagic Fever Virus (Orthonairovirus haemorrhagiae) causes a hemorrhagic fever with mortality rates reaching up to 40%. For years, this virus has maintained its position among the top priority pathogens identified by the World Health Organization (WHO). This is due to its endemic presence across a vast region-from Africa and Spain to the Balkans, the Middle East, and throughout Asia-its potential for human-to-human transmission, and the lack of an effective and approved vaccine or treatment. Therefore, the development of an effective vaccine against CCHFV is of critical importance. Building on the success of mRNA-based vaccines during the Coronavirus Disease 2019 (COVID-19) pandemic, this study reports the development of a messenger ribonucleic acid (mRNA) vaccine candidate expressing the nucleocapsid protein (NP) of CCHFV. The CCHFV NP in vitro transcript (IVT) was designed with pseudouridine (Psi) nucleoside modification. As part of the preclinical characterization of the IVT vaccine candidate, the biochemical and immunological properties of NP were confirmed in Huh-7 cells transfected with IVT NP-Psi mRNA. Afterwards, the efficacy of IVT NP-Psi mRNA immunization was evaluated in immunocompetent BALB/c and transiently immunosuppressed (IS) C57BL/6 mice. In CCHFV challenge studies, IS C57BL/6 mice were used. IS C57BL/6 mice were immunized intramuscularly with 2 doses of IVT NP- Psi mRNA, either naked or encapsulated in Poly(lactic-co-glycolic acid) (PLGA) nanoparticles, administered 14 days apart. High levels of CCHFV NP-specific humoral (IgM and IgG) and cellular (cytokine and lymphoproliferative) responses were demonstrated in BALB/c mice immunized with IVT NP- Psi mRNA. In challenge experiments, 100% survival was observed with both the naked and PLGA-encapsulated IVT NP-Psi mRNA immunizations. These findings demonstrate 100% survival following lethal CCHFV challenge under the experimental conditions tested in this mouse model and support the potential of NP-encoding pseudouridine-modified mRNA vaccines. Additionally, 100% survival was observed in mice immunized with inactivated CCHFV, whereas only 20% survival was detected in the unmodified IVT NP-mRNA vaccinated animals. In the protected mice, viral clearance was observed in the spleen, liver tissues, and blood on day 14 post-challenge. This study demonstrates that NP, the most abundant protein of the virus, is capable of providing significant survival benefits in the tested mouse model. Furthermore, our report represents a significant step in identifying a potential vaccine candidate and provides a solid foundation for further preclinical studies necessary to support future clinical development.
Keywords: cell-mediated immunity; Crimean-Congo hemorrhagic fever virus; cytokines; disease control; humoral immunity; immune responses; virus classification; vaccines/vaccine strains; cell-mediated immunity; Crimean-Congo hemorrhagic fever virus; cytokines; disease control; humoral immunity; immune responses; virus classification; vaccines/vaccine strains